New dimensions in foreign policy: a study in British administrative experience - Beloff, Max (London, 1961)
THE present volume seeks to contribute to the under standing of one of the most important political developments of our times, the impact upon the administration and political systems of independent States of the network of international organizations in whose work they are increasingly involved. For this purpose a study has been made of one particular example; namely the effect on British Government of Britain's adherence to the family of inter national organizations which came into being in the years immediately after the Second World War in order to meet some of the most urgent needs of Western Europe, and which gave expression to the growing sense of community among the western European and north-Atlantic peoples.
Keywords: Great Britain - foreign relations